2020
DOI: 10.1186/s43042-020-00099-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 susceptibility: potential of ACE2 polymorphisms

Abstract: Background Angiotensin-converting enzyme 2 (ACE2) is a metallopeptidase that primarily functions as a negative regulator of renin angiotensin system (RAS) by converting angiotensin II (Ang II) to angiotensin 1-7. Contrary to this, another RAS component, angiotensin-converting enzyme (ACE) catalyzes synthesis of Ang II from angiotensin I (Ang I) that functions as active compound in blood pressure regulation. This indicates importance of ACE/ACE2 level in regulating blood pressure by targeting An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 57 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…Notably, ACE2 level of expression, which differs among people, could correlate with susceptibility to the infection ( Devaux et al, 2020 ). Polymorphisms of regulatory and non-coding regions such as promoters or 3’-UTR in ACE2 can have a role in the different expression levels of ACE2 among individuals ( Chaudhary, 2020 ; Lippi et al, 2020b ). Association between some mutation of ACE2 (affecting its expression) with the SARS-CoV intake was also strengthened the possible effect of ACE2 variant on SARS-CoV-2 entrance ( Lippi et al, 2020a ).…”
Section: The Role Of Ace2 Variants In Sars-cov-2 Infection and Severimentioning
confidence: 99%
“…Notably, ACE2 level of expression, which differs among people, could correlate with susceptibility to the infection ( Devaux et al, 2020 ). Polymorphisms of regulatory and non-coding regions such as promoters or 3’-UTR in ACE2 can have a role in the different expression levels of ACE2 among individuals ( Chaudhary, 2020 ; Lippi et al, 2020b ). Association between some mutation of ACE2 (affecting its expression) with the SARS-CoV intake was also strengthened the possible effect of ACE2 variant on SARS-CoV-2 entrance ( Lippi et al, 2020a ).…”
Section: The Role Of Ace2 Variants In Sars-cov-2 Infection and Severimentioning
confidence: 99%
“…Such response cytokine storm was showed in ACE2-positive cells. Thus, differences in response to COVID-19 associated with genetic polymorphism within the genes responsible for the synthesis of cytokines and pro-inflammatory mediators along with ACE2 [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their study finds a moderate variation of ACE2 expression in different population [33] and remarkably, they revealed a positive correlation between the presence of higher allelic frequency and elevated tissue expression of ACE2 in East Asian population, but no ACE2 mutant was found to resist viral binding to host cell [33]. As various studies and reviews have not identified any specific relation between ACE2 SNP (Single Nucleotide Polymorphism) and severity of COVID 19 in various ethnic groups yet, so further screening is needed [34].…”
Section: Genetic Factorsmentioning
confidence: 94%